Aberrant trafficking of a Leu89Pro connexin32 mutant associated with X-linked dominant Charcot–Marie–Tooth disease. (2nd October 2016) - Da, Yuwei; Wang, Wei; Liu, Zhongfeng; Chen, Hai; Di, Li; Previch, Lauren; Chen, Zhiguo
Abstract : Objective: To determine the functional abnormalities of the Leu89Pro mutation in connexin32 (CX32), which we have previously reported is present within an X-linked dominant Charcot–Marie–Tooth disease family. In this family, male patients were moderately to severely affected. Methods: We performed immunofluorescence to investigate whether the Leu89Pro CX32 protein was transported to the cell membrane in HeLa and Schwann cells. First, we constructed the eukaryotic express plasmids expressing CX32 (wild-type or Leu89Pro) and enhanced green fluorescent protein by the gene recombination technology. Then the recombinant plasmids were transiently transfected into communication-incompetent HeLa cells and human Schwann cells by the lipofectamine method. Later, we double-labeled cells for both CX32 and markers of the ER (calnexin) or the Golgi (58-kDa protein) at 24 h or 48 h. The images were collected using a Leica TCS SP5 II confocal microscope. Results: The mutant CX32 protein was localized in the endoplasmic reticulum and failed to reach the cell membrane to form gap junctions. Conclusion: Our results indicated that the Leu89Pro substitution in the second transmembrane domain of CX32 disrupts the trafficking of the protein, inhibiting the assembly of CX32 gap junctions, which in turn may result in peripheral neuropathy. This functional abnormality may explain the moderate to severe phenotype seen in Leu89Pro patients, and as such represents a promising therapeutic target in the treatment of this subset of CMTX patients.